2017
DOI: 10.4103/1119-3077.164354
|View full text |Cite
|
Sign up to set email alerts
|

Impact of informed consent on patient decisions regarding third molar removal

Abstract: Increased anxiety was not associated with the order in which information was presented in the informed consent form. However, the informed consent form itself was a major contributor to increased patient anxiety. Further studies regarding the contents of consent forms and their effects on patient anxiety and decisions regarding third molar removal are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…This suggests a greater tendency toward the impaction of these teeth, corroborating with studies that show that mandibular third molars have a much greater chance of impaction than do other teeth. 13,14 By contrast, maxillary third molars present a greater GC length, illustrating a longer course to be covered until its eruption on the alveolar ridge, thus favoring its impaction in the vertical direction. Alfadil and Almajed 15 conducted a study aimed at registering the pattern of the impaction of third molars, and concluded that the vertical angulation was more prevalent in the maxilla (56.5%) and the mesioangular angulation in the mandible (40.5%).…”
Section: Discussionmentioning
confidence: 99%
“…This suggests a greater tendency toward the impaction of these teeth, corroborating with studies that show that mandibular third molars have a much greater chance of impaction than do other teeth. 13,14 By contrast, maxillary third molars present a greater GC length, illustrating a longer course to be covered until its eruption on the alveolar ridge, thus favoring its impaction in the vertical direction. Alfadil and Almajed 15 conducted a study aimed at registering the pattern of the impaction of third molars, and concluded that the vertical angulation was more prevalent in the maxilla (56.5%) and the mesioangular angulation in the mandible (40.5%).…”
Section: Discussionmentioning
confidence: 99%